The motivations and barriers of landowner participation in reforestation on in the Bellbird Biological Corridor in Costa Rica - Powlen, Kathryn, author; Jones, Kelly, advisor; Taylor, Peter Leigh, committee member; Bright, Alan, committee member (Colorado State University. Libraries, 2018)
Forest conservation and restoration approaches are implemented to address the decline in global forest cover, yet face institutional and social challenges in reaching end goals. A number of external and internal motivators can influence landowner participation in conservation, but there is still a lack of information on the relative influence of these types of motivators on decision making. This research examines the role of internal and external motivations and barriers on farmer participation in reforestation in the tropics. Eighty-five household surveys and 18 in-depth interviews were conducted with farmers in Costa Rica in 2017. Internal motivations analyzed include farmers' perceptions of environmental, economic and social outcomes of reforestation. External motivations analyzed include perceived support from conservation organizations. Multiple regression models were used to determine the significance of these factors, along with household and biophysical characteristics, on reforestation participation. External support and environmental perceptions were the most consistently significant variables across all regression models. Farm size and the number of years spent on the property also significantly influenced the decision to plant trees. Regression results were triangulated and contextualized with interview data. Results suggest that farmers are primarily concerned about securing regulating ecosystem services, such as water quality and quantity. Respondents showed a preference for in-kind support over cash. Interview data identified a lack of technical knowledge on how to plant trees and appropriate species to plant, unsuccessful past experiences and a lack of trust in external organizations as barriers to reforestation. Overall, this research suggests that both internal and external motivators influence the decision to participate in reforestation, and that those motivators are moderated by contextual factors. Management implications suggest future extension programs which focus on outreach and environmental education will be important for the success of reforestation projects in the study area. Overcoming the initial cost to plant trees and promoting ecosystem services values from tree planting will be important components of future reforestation project design.